46.3k views
0 votes
If f(x) - 4x2-3 and g(x) = x+1, find (f - g)(x).

O A. x - 4x2 - 2
O B. 4x - 3
O C. 4x2 - X-4
O D. 4x2 - X-2

User Scrot
by
6.0k points

2 Answers

2 votes

Answer:

C

Explanation:

4x^2 - 3 - (x+1)

Distribute the -

4x^2 - 3 - x -1

=4x^2-x-4

So c

User SamClem
by
6.4k points
1 vote

Answer:

4x^2-x-4

Explanation:

f(x) = 4x^2-3 and g(x) = x+1,

(f - g)(x)= 4x^2-3 -( x+1)

Distribute the minus sign

=4x^2-3 - x-1

Combine like terms

=4x^2-x-4

User Maxim Kirilov
by
6.6k points